Using emotional intelligence in coaching high-performance athletes: a randomised controlled trial - Barlow, A.; Banks, A. P. (Coaching: An International Journal of Theory, Research and Practice, 2014)
Emotional intelligence is an important and popular concept within coaching. This randomised controlled trial investigated the short-term impact of coaching using emotional intelligence on three factors related to performance in athletes: anxiety, self-efficacy and team identification. Twenty high-performance netball players were divided into coaching and control groups. The coaching group completed the Bar-On EQ-i to produce emotional intelligence profiles that formed the basis of the solution-focused coaching session. Coaching improved self-efficacy and anxiety but not team identification. There was no change in the control group. Self-efficacy and anxiety are directly linked to scales on the EQ-i whereas team identification is not directly linked. The findings indicate that solution-focused coaching using emotional intelligence is effective, but only when a direct link is identified between a particular component of emotional intelligence and a particular outcome.